Proper Names as an Ethnocultural Text: Nogai Place Names as Determinants of Ethnic Memory - Bulgarova, Mariia (Lietuvos istorijos studijos, 2023)
The toponymy of any region contains information about the most important stages in the history of the material and spiritual culture of the people, behind each geographical name there is a historical reality. The toponymic system of each language in verbalized form reflects the historical, social, linguistic and ethno-cultural features of the ethnic group. Toponyms can exist on the map for a long time and remain relevant throughout the history of the people. The migration routes of the Nogais in the expanses of Eurasia are marked by toponyms preserved on maps of many historical territories and states, in archives and written monuments, oral folk art, ethnic memory of peoples. Nogai toponyms are scattered – from the Irtysh to the Danube, from Issyk-Kul to the Mediterranean Sea. In the toponymy of Eurasia, a significant trace was left by the eponym Nogai, immortalized in time and space. Geographical names with the name Nogai are recorded in the toponymy of different peoples inhabiting Russia and abroad in the toponymy of Adygea and North Ossetia, Kabardino-Balkaria and Karachay-Cherkessia, Bashkortostan and Tatarstan, Central Asia. Nogai ethnonyms have been preserved in the names of numerous settlements in Türkiye. The ma- terial given by the author in this article has a huge cultural potential, declares the fact of the cultural and historical value of each geographical name.